Oviposition activity of Aedes aegypti in a temperate city of Argentina and its implications on local transmission of dengue - González, Lucía Fernanda (2022)
The global incidence of the disease caused by the dengue virus has significantly increased throughout the last decades, becoming an emerging public health issue. Buenos Aires City, located in the temperate region of Argentina, has been affected by dengue epidemics during 2009, 2016 and 2020, with increasing number of cases. The main vector of dengue and other diseases such as Zika, Chikungunya fever and yellow fever is the mosquito Aedes aegypti, and the transmission of dengue is expected to be positively related to the abundance of this vector. The aim of this study is to analyze how the incidence of dengue cases during the last epidemic of dengue is related to the abundance of Aedes aegypti in different administrative districts within Buenos Aires City.